Echocardiography and monitoring patients receiving dopamine agonist therapy for hyperprolactinaemia: A joint position statement of the British Society of Echocardiography, the British Heart Valve Society and the Society for Endocrinology. (28th February 2019) - Steeds, Richard; Stiles, Craig; Sharma, Vishal; Chambers, John; Lloyd, Guy; Drake, William
Summary: This is a joint position statement of the British Society of Echocardiography, the British Heart Valve Society and the Society for Endocrinology on the role of echocardiography in monitoring patients receiving dopamine agonist (DA) therapy for hyperprolactinaemia. Evidence that DA pharmacotherapy causes abnormal valve morphology and dysfunction at doses used in the management of hyperprolactinaemia is extremely limited. Evidence of clinically significant valve pathology is absent, except for isolated case reports around which questions remain. Attributing change in degree of valvar regurgitation, especially in mild and moderate tricuspid regurgitation, to adverse effects of DA in hyperprolactinaemia should be avoided if there are no associated pathological changes in leaflet thickness, restriction or retraction. Note must be taken that even where morphological change in leaflet structure and function may be suspected, grading is semi‐quantitative on echocardiography and may vary between different machines, ultrasound settings and operators. Decisions regarding discontinuation of medication should only be made after review of serial imaging by an echocardiographer experienced in analysing drug‐induced valvulopathy or carcinoid heart disease. A standard transthoracic echocardiogram should be performed before a patient starts DA therapy for hyperprolactinaemia. Repeat transthoracic echocardiography should then be performed at 5 years after starting cabergoline in patients taking a total weekly dose less than or equal to 2 mg. If there has been no change on the 5‐year scan, repeat echocardiography could continue at 5‐yearly intervals. If a patient is taking more than a total weekly dose of 2 mg, then annual echocardiography is recommended.